PANDANGAN DUNIA PENGARANG DAN KESALEHAN SOSIAL DALAM KUMPULAN PUISI RAHMAN RAHIM CINTA KARYA EMHA AINUN NADJIB - Julianto, Indra Rasyid; Supriyanto, Teguh; Doyin, Mukh (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Poetry is one of the literary works that has the principle of free expression. Through poetry, one can express many things by focusing on language as a meaning that can represent many things. One of them is Emha Ainun Nadjib's poetry, which is collected in the poetry anthology Rahman Rahim Cinta. The research conducted is on the author's worldview and social piety. It was found that there are five author's worldviews and also four social piety that have strong meaning in the process of creating works. This research was conducted through heuristic and hermeneutic data analysis and the study of literary sociology which is essentially a discipline that connects sociology with literature that has similar objects, namely humans in society, used as an approach, which is strongly supported by the theory of genetic structuralism in the search for meaning.